Digitalization of the Project Citizen Learning Model on Students' Citizenship Skills - Apriyanda Kusuma Wijaya; Dadang Sundawa; Sapriya Sapriya (Indonesian Journal Publisher in cooperation with Indonesian Social Studies Association (APRIPSI), 2025)
Civic education in the digital era enables learning models that incorporate digital media, leading to changes in the way learning occurs. Adaptation of the project citizen learning model to incorporate digital media is necessary to support the development of students' citizenship skills. The purpose of this study was to investigate the impact of digitalizing the project citizen learning model on students' citizenship skills. This study employed a quasi-experimental design with a one-group pretest and posttest. The population in this study consisted of 78 students from Madinatunnajah Islamic High School and 108 students from PGRI Babakan Senior High School. The sampling technique employed was purposive sampling, specifically involving 21 students from Class XI at Madinatunnajah Islamic High School in Cirebon City, and 36 students from Class XI at PGRI Babakan Senior High School in Cirebon Regency. The results of this study are the effect of implementing the digitalization of the project citizen learning model on students' citizenship skills.